Ink, stink bait, revenge, and Queen Elizabeth : a Yorkshire yeoman's household book - May, Steven W.; Marotti, Arthur F., 1940- (A Yorkshire yeoman's household book, 2014)
In Ink, Stink Bait, Revenge, and Queen Elizabeth, Steven W. May and Arthur F. Marotti present a recently discovered "household book" from sixteenth-century England. Its main scribe, John Hanson, was a yeoman who worked as a legal agent in rural Yorkshire. His book, a miscellaneous collection of documents that he found useful or interesting, is a rare example of a middle-class provincial anthology that contains, in addition to works from the country's cultural center, items of local interest seldom or never disseminated nationally. Among the literary highlights of the household book are unique copies of two ballads, whose original print versions have been lost, describing Queen Elizabeth's procession through London after the victory over the Spanish Armada; two poems attributed to Elizabeth herself; and other verse by courtly writers copied from manuscript and print sources. Of local interest is the earliest-known copy of a 126-stanza ballad about a mid-fourteenth-century West Yorkshire feud between the Eland and Beaumont families. The manuscript's utilitarian items include a verse calendar and poetic Decalogue, model legal documents, real estate records, recipes for inks and fish baits, and instructions for catching rabbits and birds. Hanson combined both professional and recreational interests in his manuscript, including material related to his legal work with wills and real estate transactions. As May and Marotti argue in their cultural and historical interpretation of the text, Hanson's household book is especially valuable not only for the unusual texts it preserves but also for the ways in which it demonstrates the intersection of the local and national and of popular and elite cultures in early modern England